Power to Punish Norm Violations Affects the Neural Processes of Fairness-Related Decision Making - Cheng, Xuemei; Zheng, Li; Li, Lin; Guo, Xiuyan; Wang, Qianfeng; Lord, Anton; Hu, Zengxi; Yang, Guang (Frontiers in Behavioral Neuroscience, 2015)
Punishing norm violations is considered an important motive during rejection of unfair offers in the Ultimatum Game (UG). The present study investigates the impact of the power to punish norm violations on people’s responses to unfairness and associated neural correlates. In the UG condition participants had the power to punish norm violations, while an alternate condition, the Impunity Game (IG), was presented where participants had no power to punish norm violations since rejection only reduced the responder’s income to zero. Results showed that unfair offers were rejected more often in UG compared to IG. At the neural level, anterior insula and dorsal anterior cingulate cortex were more active when participants received and rejected unfair offers in both UG and IG. Moreover, greater dorsolateral prefrontal cortex activity was observed when participants rejected than accepted unfair offers in UG but not in IG. Ventromedial prefrontal cortex activation was higher in UG than IG when unfair offers were accepted as well as when rejecting unfair offers in IG as opposed to UG. Taken together, our results demonstrate that the power to punish norm violations affects not only people’s behavioral responses to unfairness but also the neural correlates of the fairness-related social decision-making process.